Prospects of School Social Work in Haor Areas of Bangladesh - Parveen, Syeda Sultana (Advances in Social Sciences Research Journal, 2021)
This study employs qualitative research methods to explore the performance of school students in reading motivation, sincerity, and achievement and the perceived role of a school social worker in Tanguar Haor inhabitants of rural Sunamganj in Bangladesh. Findings of the study suggest that the stakeholders in rural education in haor areas are keen to see the students’ achievements in reading, motivation, and academic performance but unaware of how to improve. This paper argues that social workers have a significant role to play in rural areas, particularly in remote places like haor areas, to enhance students’ performances and academic achievements in the school as well as to improve the quality of education services in those areas.